Attitude and Perception of Rural Women towards the Formation and Membership of Self-Help Groups in Kaduna State, Nigeria - Ezeh, C. C; Ezeh, O. H (Asian Journal of Agriculture and Rural Development, 2016)
This study was carried out to elicit the attitude and perception of rural women in Kaduna State, Nigeria, towards the formation and membership of self-help groups (SHGs). Multistage random sampling was adopted and a total of 176 respondents from two (2) local government areas were interviewed using a pre-tested structured questionnaire. Two sets of questions based on a 5-point Likert-type scale were used to generate primary data. The respondents expressed over whelming positive attitude to the formation and membership of SHGs as indicated by the aggregate and mean scores which ranged from 607 to 719 and 345 to 4.08 respectively. Age (r = 0.310, P<0.05) and educational levels (r = –0.341, P<0.01) significantly influenced membership of SHGs while man tal status and family size did not. Recommendations are proffered with a view to sensitizing the womenfolk and enhancing their pro-active involvement in SHGs in their localities.